Epidemiology and Rb1 gene of retinoblastoma - Yun, Jun (International Journal of Ophthalmology Press, 2011)
Retinoblastoma (Rb) is the most common eye cancer in children and it can be inherited. Rb is quite rare and originators from the neural retina with a significant genetic component in etiology, which occurs in approximately 1 in every 20 0000 births. In children with the heritable genetic form of Rb, there is a mutation on chromosome 13, called the retinoblastoma 1 (Rb1) gene. Early diagnosis and intervention is critical to the successful treatment of the Rb. The Rb1 gene is the first cloned tumor suppressor gene. As a negative regulator of the cell cycle, Rb1 gene could maintain a balance between cell growth and development through binding to transcription factors and regulating the expression of genes involved in cell proliferation and differentiation. Thus, it is involved in cell cycle, cell senescence, growth arrest, apoptosis and differentiation. We summarized the recent advances on the epidemiology and Rb1 gene of Rb in this review.